Efektifitas Waktu Pengendalian Gulma dan Penggunaan Mulsa Jerami Padi Terhadap Pertumbuhan dan Hasil Tanaman Kedelai Edamame (Glycine max (L.) - Muhammad Rizki Saputra; Sarman Sarman; Rainiyati Rainiyati; Elly Indra Swari (Universitas Batanghari, 2024)
Soybeans are one of the important food crop commodities in Indonesia and have strategic value because they are able to supply the nutritional needs of the community and as a source of income for farmers. One of the causes of low edamame soybean cultivation is low production caused by the presence of weeds in the cultivation area. The aim of this research is to find out how effective the use of rice straw mulch and weed control is to increase the growth and yield of edamame soybean plants. A factorial Randomized Block Design (RBD) was used for this research. The first factor in RAK is the weed control time with three levels, namely p0 = no control, p1 = 2x control (18 DAP and 36 DAP), and p2 = 1x control (32 DAP). The second factor is the use of straw mulch with three levels, namely m0= no mulch, m1= 5 tons/ha of straw mulch, and m2= 10 tons/ha of straw mulch. Observed variables included plant height, flowering age, number of primary branches per plant, number of pods per plant, and fresh pod weight. The research results show that using five tons of mulch per ha and controlling weeds once can increase the yield and growth of edamame soybeans while reducing weed growth. Kata Kunci: Pengendalian Gulma, Kedelai Edamame, Mulsa Jerami